Serum Growth Differentiation Factor 15 is Negatively Associated with Leukocyte Telomere Length - Jie Yu; Yiwen Liu; Huabing Zhang; Fan Ping; Wei Li; Lingling Xu; Yuxiu Li (The Journal of Nutrition, Health and Aging)
Background: Telomere length(TL)and mitochondrial DNA copy number(mtDNAcn) are classic biomarker of aging. Recently, growth differentiation factor 15(GDF15) has attracted considerable attention as a vital component in the aging process. Methods: The present study aimed to study the relationship between GDF15 and telomere length and mtDNAcn.This was a cross-sectional analysis nested in a longitudinal cohort study conducted in Changping District, Beijing, from 2014 to 2021. Serum GDF15,leukocyte lelomere length(LTL) and mtDNAcn were determined in 802 subjects.LTL and mtDNAcn was quantified by real-time PCR assay. Multivariate linear regression and restricted cubic spline diagram were used for statistical analysis. Results: Subjects with higher GDF15 were older,had larger waist circumference, higher systolic blood pressure and glycated hemoglobin A1c (HbA1c),shorter LTL and tended to had less mtDNAcn. In correlation analysis, GDF15 was positively correlated with age, while LTL and mtDNAcn were negatively correlated with age.After adjusting for confounding factors,GDF15 was negatively associated with LTL (β = −0.120, 95%CI [−0.197, −0.042], p = 0.003) and the association was linear(p for nonlinear = 0.645), while the negative association between GDF15 and mtDNAcn did not reach significance.In the stratified analyses,the negative associations between GDF15 and LTL were more prominent in women, overweight individuals, or subjects with abnormal glucose tolerance (AGT), but similar results were observed in younger and older subjects. Conclusions: This study found a linear negative association between GDF 15 and LTL,which was more prominent in women, overweight or AGT subjects.These results supported that GDF15 might be a reliable biomarker of aging.